Compatibility of fungicides with spinosad against fruit rot and pod borer in chilli - K. MANASA, CH. RAJA GOUD* and (Indian Phytopathology, 2013)
A comprehensive study was carried on compatibility studies among selected entomopathogenic fungi, insecticides and fungicides in chilli from 2006-09 at Directorate of Oil Seeds Research (DOR), AICRP on Biological Control and Department of Entomology, College of Agriculture, Rajendranagar, Hyderabad. The effect of test insecticides viz., propiconazole ( 0.76 ppm), chlorothalonil (11.85 ppm), azoxystrobin (1.92 ppm) and tebuconazole (8.26 ppm) in combination with spinosad (ppm) on the inhibition of spores at their respective LC50 values revealed that all the combinations showed antagonism. When propiconazole 0.76 ppm (LC50) and azoxystrobin 1.92 ppm (LC50) mixed with spinosad (75, 112.5, 150, 187.5 and 225 ppm) resulted into synergistic effect on inhibition of germination of spores, whereas chlorothalonil and tebuconazole showed antagonistic effect when mixed with spinosad at above concentrations. Similarly, the spinosad (LC50) mixed with four fungicides at their respective LC50 values were studied for their effect on third instar larvae of H. armigera and all of them showed synergistic effect except propiconazole. Spinosad at 11.85 ppm (LC50) combined with propiconazole (750, 1000, 1250 and 1500 ppm), chlorothalonil (1500, 2000, 2500 and 3000 ppm), azoxystrobin (750, 1000, 1250 and 1500 ppm) and tebuconazole (750, 1000, 1250 and 1500 ppm) showed synergism against third instar larvae of H. armigera.